Behcets Disease: Presented with Genital Ulcer (Journal of Enam Medical College, 2015)
Behcets disease which can affect almost every organ system of the body and is diagnosed mainly clinically is a rare condition. The presence of certain clinical features, elimination of other possible causes of patients symptoms and if possible proof of vasculitis by biopsy of an involved tissue supports a diagnosis. We report a young female presented with 7-day history of vulval ulcer and erythema nodosum. Diagnosis was made according to International Study Group criteria for Behcets disease and histological findings. She was treated with corticosteroid, colchicine and dapsone which caused significant clinical improvement. We report this case to increase awareness among physicians on Behcets disease to improve its management.J Enam Med Col 2015; 5(3): 175-178